COOKING CLASS DENGAN PENDEKATAN DEEP LEARNING UNTUK KEMAMPUAN MOTORIK HALUS ANAK. - Salsabillah, Talya; Imtihana, Aida; Oktamarina, Lidia; Mardeli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was initiated by the low level of fine motor skills among Group B children at TK IT Cipta Harapan Palembang, particularly in aspects of hand-eye coordination, manipulation accuracy, and finger movement control. The lack of engaging, contextual, and continuous learning activities was identified as one of the contributing factors. Cooking class activities based on a deep learning approach, which involve stirring, squeezing, pouring, molding, and decorating food, are believed to improve children’s fine motor skills through direct and meaningful learning experiences. The method used in this study was quantitative with a pre-experimental one group pretest–posttest design. The research population consisted of 14 Group B children, all of whom were selected as the sample using a total sampling technique. Data were collected through observation, tests, and documentation. Data analysis included validity, reliability, and normality tests, as well as a paired sample t-test. The results showed a significant effect of deep learning-based cooking class activities on children’s fine motor skills. This was evidenced by a t-count value of -27.571. With a degree of freedom (df) of 13 and a significance level of 5% (0.05), the t-table value was ±2.131. Since |t-count| > t-table (27.571 > 2.131), the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. This indicates a significant effect of deep learning-based cooking class activities on improving fine motor skills of Group B children at TK IT Cipta Harapan Palembang.